Produtividade, nutrição mineral e teores de metais pesados no solo e em girassol adubado com lodo de esgoto - Altina Lacerda Nascimento (2012)
The objective of this study was to evaluate the contents of nutrients and heavy metals in soil and plant, the productivity of sunflower and soil properties in response to fertilization with sewage sludge under different stabilization processes. The experiment was conducted in Haplic Cambisol, with the treatments: control (without fertilization), fertilization with sewage sludge solarized, fertilization with compost sewage sludge, fertilization with sewage sludge vermicomposted, fertilization with limed sewage sludge and chemical fertilizer recommended for culture. It was used a randomized block design with four repetitions. The different forms of treatment of sewage sludge did not affect the productivity; however, the application of sewage sludge, regardless of the stabilization method used it showed to be more effective than chemical fertilizer and the control treatment. Overall, fertilization with compost sewage sludge limed provided higher contents of nutrients in the soil. The treatments with compost sewage sludge and vermicomposted had higher leaf nutrient contents, except for N. The petiole of sunflower was sensitive only to variation in levels of N and P in the soil. The sewage sludge did not affect the organic matter content, pH, SB, V%, CTC(t), CTC(T) and the contents of H + Al when compared to chemical fertilizer and treatment without fertilization, except the limed sewage sludge, which increased the pH, SB, CEC and V% (t) of the soil. Independent of stabilization, the application of sewage sludge did not affect the concentrations of Cu, Cr, Cd and Ni from the soil, but increased levels of Zn. Also, the application of sewage sludge solarized and of the limed sewage sludge increased the content of Pb in soil. In general, the levels of heavy metals in the leaf and petiole of sunflower were not influenced by the application of sewage sludge. Considering that the productivity did not vary with the forms of stabilization of sewage sludge, it is recommended the use of sewage sludge to be solarized for the stabilization process that spends less time and labor